Combined Treatment with Acalabrutinib and Rapamycin Inhibits Glioma Stem Cells and Promotes Vascular Normalization by Downregulating BTK/mTOR/VEGF Signaling - Yu-Kai Su; Oluwaseun Adebayo Bamodu; I-Chang Su; Narpati Wesa Pikatan; Iat-Hang Fong; Wei-Hwa Lee; Chi-Tai Yeh; Hsiao-Yean Chiu; Chien-Min Lin (MDPI AG, 2021)
Glioblastoma (GBM) is the most common primary malignant brain tumor in adults, with a median duration of survival of approximately 14 months after diagnosis. High resistance to chemotherapy remains a major problem. Previously, BTK has been shown to be involved in the intracellular signal transduction including Akt/mTOR signaling and be critical for tumorigenesis. Thus, we aim to evaluate the effect of BTK and mTOR inhibition in GBM. We evaluated the viability of GBM cell lines after treatment with acalabrutinib and/or rapamycin through a SRB staining assay. We then evaluated the effect of both drugs on GBM stem cell-like phenotypes through various in vitro assay. Furthermore, we incubated HUVEC cells with tumorsphere conditioned media and observed their angiogenesis potential, with or without treatment. Finally, we conducted an in vivo study to confirm our in vitro findings and analyzed the effect of this combination on xenograft mice models. Drug combination assay demonstrated a synergistic relationship between acalabrutinib and rapamycin. CSCs phenotypes, including tumorsphere and colony formation with the associated expression of markers of pluripotency are inhibited by either acalabrutinib or rapamycin singly and these effects are enhanced upon combining acalabrutinib and rapamycin. We showed that the angiogenesis capabilities of HUVEC cells are significantly reduced after treatment with acalabrutinib and/or rapamycin. Xenograft tumors treated with both drugs showed significant volume reduction with minimal toxicity. Samples taken from the combined treatment group demonstrated an increased Desmin/CD31 and col IV/vessel ratio, suggesting an increased rate of vascular normalization. Our results demonstrate that BTK-mTOR inhibition disrupts the population of GBM-CSCs and contributes to normalizing GBM vascularization and thus, may serve as a basis for developing therapeutic strategies for chemoresistant/radioresistant GBM.